THE USE OF SOCIAL MEDIA AS TOOL TO PROMOTE BEACH TOURISM IN AKKARENA BEACH - Nurul Ayu Istiqamah (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This study aims to analyze the use of social media as a promotional tool to enhance the attractiveness of Akkarena Beach, located in Makassar City. Digital promotion through social media has become a crucial strategy in strengthening destination branding and attracting tourists, especially in the era of rapidly evolving information technology. The research focuses on the effectiveness of social media in delivering tourism information, the types of content that most appeal to audiences, and the most influential platforms in promoting Akkarena Beach. Despite its natural beauty and available tourism facilities, Akkarena Beach still faces challenges such as the lack of a targeted promotional strategy, limited involvement of local stakeholders in digital content creation, and outdated online information. This study uses a qualitative case study approach, employing observation, interviews, and content analysis of social media related to the destination. Data were analyzed using a SWOT approach to identify strengths, weaknesses, opportunities, and threats in utilizing social media as a promotional medium. The findings show that key strengths include the beach’s scenic appeal, accessibility, and strong visual potential for digital content, while weaknesses involve inconsistent content and low participation from local actors. Opportunities arise from the growing trend of visual-based tourism promotion and government support for digitalization programs, while threats include competition from other destinations that are more active on social media. The study concludes that creative, collaborative, and sustainable promotional strategies are essential in leveraging social media to improve the visibility and competitiveness of Akkarena Beach as a leading beach tourism destination.